"Sustainable self-compacting concrete containing waste ceramic tile aggregates: Fresh, mechanical, durability, and microstructural properties". (1st October 2022) - Meena, Ram Vilas; Jain, Jinendra Kumar; Beniwal, Ankit Singh; Chouhan, Harshwardhan Singh
Abstract: In construction industry, the use of ceramic materials is rising continuously in the form of sanitary fittings, ceramic tiles, and electrical insulators etc. The ceramic manufacturing industry necessarily generates wastes, categorical of the newly introduced developments in manufacturing processes. During processing, fixing and transportation, the brittle nature of ceramic materials adds to the waste generation in large amounts. Use of all this waste in making of self-compacting concrete (SCC) can help with waste management along with improving the properties of SCC. Hence, in this study, fresh properties, mechanical strength, durability and microstructure of SCC containing waste ceramic tile (WCT) were examined. Six SCC mixes were prepared using crushed WCT as a substitution of natural river sand (NRS). The use of waste ceramic tile as a partial and full substitution (0%, 20%, 40%, 60%, 80% and 100%) of NRS of SCC was examined. The fresh SCC properties tests performed were Slump-flow, T500 time, V-funnel, U- box, J-ring and L-box test, while the mechanical and durability properties were assessed by compressive strength, flexural strength, split tensile strength, water absorption, water permeability and ultrasonic pulse velocity tests. The fresh properties of all mixes were found within limits prescribed by EFNARC. The integration of WCT in SCC mixtures found increase in the compressive, flexural and split tensile strength at 60% substitution and further substitution led to reduction in all strength of SCC. The superior ultrasonic pulse velocity values and higher impermeability characteristics of waste ceramic based SCC mixtures were found till 100% incorporation of WCT, when compared to the reference SCC mix. The microstructural study using Fourier transform infrared radiation (FTIR) technique, X-ray diffraction (XRD), Scanning Electron Microscope (SEM) was performed on hardened SCC to know in depth behavior of waste ceramic over control mix. Highlights: Ceramic tile industry generates tile waste which goes to landfills. Depleting natural aggregates can be substituted with waste ceramic tile in SCC. 100% of WCT replacement in SCC mixes can be used with excellent performance. XRD, FTIR, and SEM analysis validates higher strength of SCC with WCT.